Mental health of Psychiatric Patients’ Families in Srinagarind Hospital - Kulvechait, Amporn; Rod-ong, Duangkaew; Supataraniyapong, jarinjit; Mahaton, Sukon (Srinagarind Medical Journal, 2013)
Background : Nowadays life style of each person often faces with stress all the time. When their families were sick especially psychiatric’ families, they had to suffer and will have psychic problem if nobody help them. Objective : To study the mental health of psychiatric patient’s families, to compare mental health of out-patient’s families and in-patient’s families , to study the difference mental health of all patient’s families, Out-patient’s families and in – patient’s families by sex, age, education , status, occupation, socio-economic status, relation with patient and duration of illness. Design : A descriptive research. Setting : Srinagarind Hospital, Khon Kaen University. Subjects : 200 families of patients who ere admitted at psychiatric ward and out patient psychiatric department of Srinagarind Hospital from September to December , 1995. Measurement : General Health Questionnaire of Goldberg & Williams. Data were analyzed by using frequency, percentage and Z-test. Results : (1) The most of mental health of the patient’s families was not good approximately 62%.(2) There was no significant difference in mental health between out- patient’s families and in-patient’s families at the 0.05 level (3) There were significant differences in mental health between out-patient’s families by age, education , status, and occupation at the 0.05 level .(5) There were significant differences in mental health between in – patient’s families by age and relation with patient at the 0.05 level. Conclusion : Most of the mental health of the patients’ families was not good. So, we should promote and support mental health of the patients’ families especially in aging, low educated, agriculturist and their parents.